STRATEGIC POLICY FOR THE DEVELOPMENT OF LEADING SECTORS OF RUPAT ISLAND AS AN INDONESIA-MALAYSIA BORDER AREA - Muslim Muslim; Mahendra Romus; Muhamad Rachmadi; Rony Jaya; Riki Hanri Malau; Muklis Muklis; Mhd Rafi; larbiel Hadi (Sultan Syarif Kasim State Islamic University, Riau, 2024)
The research aims to determine the center of growth and strategic policies in developing leading sectors on Rupat Bengkalis Island, Indonesia. The research method uses a mixed-methods approach: calculations and analysis using Klassen typology, in-depth interviews, and documentation. The research results show that the agricultural and fisheries sectors are the leading sectors on Rupat Island, especially Central Rupat of the Klassen typology, with an average growth rate of 0.32 and a contribution of 49%. The government's strategic policies include improving the quality of roads connecting bridges, improving infrastructure quality, and improving the welfare of farmers and fishermen.